China’s Trade and Investment in the Western Balkans Under the Belt and Road Initiative: Focus on North Macedonia - Iskra Stanceva-Gigov, Klimentina Poposka (IGI Global, USA, 2022)
The China Belt and Road Initiative (BRI) and the 17+1 cooperation platform, as an integral part of it, is the key framework for China’s foreign policy towards most parts of the world, including the Western Balkans (WB). Through its global initiative and cooperation platform, China creates a range of opportunities for facilitating trade and increasing export, financial integration and greater Chinese investment, major infrastructure projects, as well as their funding. This chapter analyzes the real situation regarding these aspects in the WB countries, especially focused on North Macedonia. The analysis indicates that there has been some progress in co-operation, but the WB countries (excluding Serbia) have failed to maximize their interests either in bilateral co-operation or in the framework of the BRI initiative and the 17+1 platform. Conclusively, despite all the great expectations, the trade exchange, Chinese investments, and the realized infrastructure projects do not reach a significant level.
Keywords: Belt and Road Initiative; Cooperation Platform 17+1; Foreign Direct Investment; International Trade